2022
DOI: 10.1177/11786469221135545
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Kynurenine Pathway in the (Patho) physiology of Maternal Pregnancy and Fetal Outcomes: A Systematic Review

Abstract: Introduction: Tryptophan is the precursor of kynurenine pathway (KP) metabolites which regulate immune tolerance, energy metabolism, and vascular tone. Since these processes are important during pregnancy, changes in KP metabolite concentrations may play a role in the pathophysiology of pregnancy complications. We hypothesize that KP metabolites can serve as novel biomarkers and preventive therapeutic targets. This review aimed to provide more insight into associations between KP metabolite concentrations in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…Furthermore, placental TRP concentration was found to be elevated in early-onset preeclampsia while reduced in late-onset PE [47]. The concentration of placental TRP was found to be elevated in cases of early-onset preeclampsia, whereas it was observed to be reduced in cases of late-onset preeclampsia [47]. These results may explain some controversy in the findings of TRP in PE women.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, placental TRP concentration was found to be elevated in early-onset preeclampsia while reduced in late-onset PE [47]. The concentration of placental TRP was found to be elevated in cases of early-onset preeclampsia, whereas it was observed to be reduced in cases of late-onset preeclampsia [47]. These results may explain some controversy in the findings of TRP in PE women.…”
Section: Discussionmentioning
confidence: 77%
“…A comparative analysis of the placentas revealed dysregulation of TRP metabolism in the placentas of women with PE, compared to the controls [43]. Furthermore, placental TRP concentration was found to be elevated in early-onset preeclampsia while reduced in late-onset PE [47]. The concentration of placental TRP was found to be elevated in cases of early-onset preeclampsia, whereas it was observed to be reduced in cases of late-onset preeclampsia [47].…”
Section: Discussionmentioning
confidence: 99%
“…KP metabolite levels in the fetal brain are higher during the perinatal period [ 127 ], decrease in the immediate postnatal period, and remain lower in adulthood under physiological conditions [ 128 ]. A recent systematic review also indicated that physiological pregnancy requires a tight balance of KP metabolites [ 129 ]. A major source of these KP metabolites is provided from the mother to the fetus via transplacental transfer and Trp degradation in the placenta [ 128 ].…”
Section: Perinatal Kp Metabolismmentioning
confidence: 99%
“…Additionally, Carpita et al investigated the changes in KP metabolites in ASD adults, and they found significantly lower levels of Trp and QUIN and no changes in Kyn and Kyna [ 2 ]. Recently, a meta-analysis comprising all KP metabolites and keywords related to maternal pregnancy and the fetal outcome showed that an altered KP metabolite concentration is significantly related to a high risk of preeclampsia, fetal growth restriction, and preterm birth [ 129 ]. These are all considered risk factors for ASD [ 204 , 205 , 206 ].…”
Section: Perinatal Kp Metabolismmentioning
confidence: 99%
“…Furthermore, the kynurenine pathway is involved in many physiological processes, playing an important role in pregnancy, regulating the placental vascular and immune tolerance, and providing neuroprotection during pregnancy 1,2,18,19 . For instance, the functional role of IDO in the maintenance of pregnancy in the mammalian placenta was demonstrated in vivo, where inhibition of IDO resulted in pregnancy loss in mice 20 .…”
mentioning
confidence: 99%